Improving Students Understanding Of The Concept Of Sound Propagation Through Cooperative Learning The Student Team Achievement Division (STAD) In Class IV SD IMPRESS 12/79 BIRU 1Tanete Riattang, Bone District - Titin Titin (Pinisi Business Administration Review, 2021)
This study aims to find out cooperative learning is a learning model where students learn in small groups to share ideas/opinions and work together to solve problems and take responsibility individually and in groups to achieve common goals. The cooperative learning process for students is needed to express ideas and develop cognitive, affective, and psychomotor abilities to improve students' understanding in the form of science process skills including observing, classifying, predicting, and communicating. Improve students' understanding of group learning in the science learning process, it has a positive impact on students. This is in line with that, students can be interested in learning science if they are allowed to carry out activities in the science learning process through real observations or by experimental science processes that have been prepared rather than being taught verbally. The purpose of learning science in elementary schools is to develop attitudes and skills as well as the ability to increase knowledge and think critically.